Comparison of dielectric barrier discharge and radio-frequency plasma processing of carbon fibers - Z. Karoly; L. Romanszki; G. Weltz; M. Mohai; J. Moczo; Sz. Klebert (eXPRESS Polymer Letters, 2021)
Carbon fibers (CFs) are commonly applied reinforcement material in various composites to improve their mechanical, thermal, or electrical properties. The physical and chemical state of the interface, the chemical bonds, and adhesion between the fiber and matrix have a great influence on certain properties of the composite, including the mechanical ones. The originally low adhesion between the CFs and the matrix material can be improved by employing non-equilibrium plasma for surface treatment of the fiber. In the present study, we compared the effect of an atmospheric dielectric barrier discharge (DBD) and a low-pressure radio frequency (RF) plasma processing on poly(acrylonitrile) based and sized CFs in terms of surface chemistry, morphology, and adhesive properties of the treated fibers. It was found that atmospheric DBD plasma treatment induced greater changes in the surface properties of the CFs as compared to RF plasma. The DBD treated CF surface became more oxidized, increasing the O/C ratio by 30%, while reaching a twofold increase in the roughness. Surface adhesion improved after both plasma treatments, but it was significantly higher after the atmospheric DBD process.